Interest, Mindsets and Engagement: Longitudinal Relations in Science Orientations for Adolescents in Informal Science Programs. - Joy, Angelina; Mathews, Channing J.; Zhao, Mengya; Law, Fidelia; McGuire, Luke; Hoffman, Adam J.; Balkwill, Frances; Burns, Karen P.; Butler, Laurence; Drews, Marc; Fields, Grace; Smith, Hannah; et al. (Journal of Youth & Adolescence, 2023)
Little is known about the factors that influence engagement for adolescents participating in informal youth science programs. This study examined longitudinal reciprocal associations between adolescents' science engagement, interest, and growth mindset. Participants were adolescents (M = 15.06, SD = 1.82 years, 66.8% female) from the UK (n = 168) and the US (n = 299). A cross lagged path analysis indicated that participants' science growth mindset at baseline was positively related to interest, and engagement at year 1, and science interest at year 1 was positively related to growth mindset at year 2. Additionally, girls had lower science growth mindsets than boys. This evidence suggests that informal programs may encourage positive STEM trajectories by fostering engagement, growth mindset and interest.